2020
DOI: 10.1111/famp.12617
|View full text |Cite
|
Sign up to set email alerts
|

Use and Benefit of Dyadic Coping for Couple Relationship Satisfaction in Parents of Children with Autism

Abstract: Parents of children with autism spectrum disorder (ASD) are at increased risk for unsatisfying and conflict‐ridden couple relationships (i.e., marital or romantic partner relationships). There is a critical need to identify the couple‐level processes that contribute to this risk. The current study examined the use of dyadic coping, defined as the appraisals and behaviors that partners in relationships use and receive to manage stressors, and to examine whether dyadic coping mediated the association between par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
(51 reference statements)
1
9
0
Order By: Relevance
“…It could be that the couple-oriented effect has been demonstrated among wives because wives (or mothers) are usually the primary care provider, particularly in Chinese culture [ 57 ]. As providing care creates stress, dyadic coping mediated the association between parenting stress and couple relationship satisfaction [ 10 ]. This study illustrated how receiving support from one’s family could be associated with satisfaction in a marital relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be that the couple-oriented effect has been demonstrated among wives because wives (or mothers) are usually the primary care provider, particularly in Chinese culture [ 57 ]. As providing care creates stress, dyadic coping mediated the association between parenting stress and couple relationship satisfaction [ 10 ]. This study illustrated how receiving support from one’s family could be associated with satisfaction in a marital relationship.…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated that the relationship between parents declined after the birth of a child with ASD [ 8 ]. It has become evident that parents of children with ASD have a low level of relationship satisfaction, which was unrelated to socioeconomic status [ 9 , 10 ]. Lower marital satisfaction influences parenting burden and the quality of the parent–child relationship [ 8 , 11 ], quality of child caregiving and also child externalizing and internalizing symptoms [ 12 , 13 , 14 , 15 ], while a good marital relationship is an important resource for dealing with the difficulty in the challenges of raising a child with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…However, findings differed in terms of the underlying mechanisms between parenting stress, DC, and relationship satisfaction. While DC was a mediator between parenting stress and relationship satisfaction in parents of a child with ASD in one study (Putney et al, 2020), relationship satisfaction mediated the relationship between DC and parental stress in other studies on parents with a child with ASD García-Lo ´pez et al, 2016). Additionally, own relationship satisfaction was found to mediate between own supportive DC and own parental psychological well-being in both men and women (García-Lo ´pez et al, 2016).…”
Section: Child Mental Healthmentioning
confidence: 90%
“…Ways of Coping. Parents of children with attention deficit and conduct problems reported higher levels of stress and less well-being than parents of children without these problems (Gabriel & Bodenmann, 2006b) and parents of a child with ASD reported higher parenting stress than did parents of healthy children (Putney et al, 2020). These parents also reported the most unfavorable levels of DC with higher levels of negative DC and lower levels of positive DC compared to parents of nonclinically children (Gabriel & Bodenmann, 2006b;Putney et al, 2020).…”
Section: Child Mental Healthmentioning
confidence: 99%
“…In this regard, we can only draw some conclusions from related research on dyadic coping among couples dealing with different challenges concerning their child's health, though not ADHD particularly. A recent study with parents of children with autism spectrum disorder (ASD), for instance, found that parents of children with ASD experienced higher parenting stress than parents of healthy children, and they additionally reported less positive dyadic coping and greater negative dyadic coping (Putney et al, 2021). Furthermore, parents of children with inattention and externalizing behavior problems reported significantly higher stress levels in the areas of the parental relationship, individual well-being, and everyday family life, as well as less competencies in dyadic coping compared to parents of children in the control group (Gabriel & Bodenmann, 2006a).…”
Section: Associations Between Parenting Stress Couple Relationship Qu...mentioning
confidence: 99%